Stimulus und Kognition. Zur Aktivierung mentaler Raumbilder - Lameli, Alfred; Purschke, Christoph; Kehrein, Roland (Linguistik Online, 2008)
Within the context of investigations of cognitive spatial models, the study analyzes the effect of varying the informational structure of linguistic survey instruments. A group of informants was asked to draw German language areas on different types of geographic maps. First, in a quantitative approach we show how the specific informational structure of each map type influences the frequency and prominence of the named language areas. The second part of the study focuses on the localization of the mentioned language areas. Here we discuss the specific effects of each type of map and the information it contains on the localization. We also discuss general characteristics of the conceptualization of linguistic space as well as differences in the perception of the prominent language areas.